2018
DOI: 10.1186/s13046-018-0809-0
|View full text |Cite
|
Sign up to set email alerts
|

SPOP promotes ATF2 ubiquitination and degradation to suppress prostate cancer progression

Abstract: BackgroundNext-generation sequencing of the exome and genome of prostate cancers has identified numerous genetic alterations. SPOP (Speckle-type POZ Protein) is one of the most frequently mutated genes in primary prostate cancer, suggesting that SPOP may be a potential driver of prostate cancer. The aim of this work was to investigate how SPOP mutations contribute to prostate cancer development and progression.MethodsTo identify molecular mediators of the tumor suppressive function of SPOP, we performed a yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…In particular, ATF2 has been shown to be capable of activating g-globin. 27 Moreover, NRF2 has been reported to be regulated by the CUL3 ubiquitin ligase complex 28 and might be a transcriptional activator of g-globin. 29 We first tested whether SPOP regulates the amounts of any of these proteins in erythroid cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ATF2 has been shown to be capable of activating g-globin. 27 Moreover, NRF2 has been reported to be regulated by the CUL3 ubiquitin ligase complex 28 and might be a transcriptional activator of g-globin. 29 We first tested whether SPOP regulates the amounts of any of these proteins in erythroid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Speckle-type POZ Protein can inhibit the proliferation, migration, and invasion of PCa cells by promoting ATF2 ubiquitination (Ma et al, 2018). PCa-associated SPOP mutants are defective at promoting ATF2 degradation in PCa cells and contribute to facilitating PCa cell proliferation, migration, and invasion (Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Speckle-type POZ Protein can inhibit the proliferation, migration, and invasion of PCa cells by promoting ATF2 ubiquitination (Ma et al, 2018). PCa-associated SPOP mutants are defective at promoting ATF2 degradation in PCa cells and contribute to facilitating PCa cell proliferation, migration, and invasion (Ma et al, 2018). Expressing PCa-associated SPOP mutants or knocking out SPOP gives PCa cells resistance to cell death caused by stress granule inducers such as docetaxel, sodium FIGURE 9 | Decision curve analyses suggested that the model had good clinical benefits: (A) The model had higher net benefit and wider threshold probability range.…”
Section: Discussionmentioning
confidence: 99%
“…SPOP suppresses tumorigenesis and progression via regulation of cell growth, apoptosis, migration, invasion and drug resistance by targeting its downstream substrates in several types of human malignancies, including prostate, lung, gastric, liver, colon and endometrial cancers SPOP mutations and downregulation were detected in human PrCa tissues, and these mutations were also tightly correlated with a worse prognosis in patients with PrCa [61]. More importantly, extensive biochemical evidence has further indicated that SPOP functions as a tumor suppressor by promoting the degradation of oncogenic substrates in PrCa, including SRC3 [62], AR [63], TRIM24 [64], c-Myc [65], DEK [66], SENP7 [67], EglN2 [68], ATF2 [69], Cdc20 [70], ERG [71,81], BRD4 [72][73][74], PD-L1 [75] and cyclin E1 [76]. Due to the many publications and space limitations, we will not describe the tumor suppressive role that SPOP plays by promoting the ubiquitination and degradation of its substrates in PrCa in detail.…”
Section: Prostate Cancer (Prca)mentioning
confidence: 99%